Imobilização física de resíduo proveniente do tratamento de águas ácidas de uma instalação de mineração de urânio - Goda, Ricardo Tadashi (2020)
Decommissioning Unit of Caldas (UDC-INB), the first Brazilian mining facility to produce industrial scale uranium and participate in the nuclear fuel cycle, is a source of environmental concern and the subject of several researches aimed at remediation strategies of its degraded areas. The mining, crushing and milling operations of this mine ceased in 1997, after 15 years of its start. Since then, due to the geological characteristics, the site has presented acid mine drainage (DAM), a process chemically defined as an acidic solution that is produced when sulfide-containing minerals are oxidized in the presence of water and oxygen. In the case of the facility in question, acid drainage is generated in two mining waste piles and in the mine pit. Currently the only mitigatory action performed at the facility is the treatment of these waters contaminated with hydrated lime to contaminate precipitation. However, this neutralization generates another problem, the formation of a residual compound called DUCA, which consists of a calcium diuranate matrix with metal hydroxides. Since 1998 INB has deposited DUCA in the pit of the mine and in 2010 it was estimated that about 67,000 tons of this waste deposited there. The deposition of the waste under these conditions is inadequate and can generate soil, water and also resolubilize contaminants that have been precipitated in the treatment of acidic waters. Within this context, we highlight the Portland cement waste immobilization technique, which this study aimed at. The technique consists of performing procedures that reduce the potential for contamination by reducing solubility, mobility and contaminant toxicity and encapsulating the residue in a matrix of high structural integrity. Exposed the problem, this study had as main objective the immobilization in Portland CP2 cement of uranium contained in the DUCA and evaluation of the chemical stabilization power through leaching tests, besides the verification of the mechanical compressive strength. For this, specimens containing DUCA, cement and water were made in different concentrations, and the molding was performed according to ABNT-NBR 5739. The evaluated water / residue / cement (A / R / C) ratios were: (C1) 68/30/2; (C2) 66/28/6; (C3) 64/27/9; (C4) 56/24/20; (C5) 47/20/33; (C6) 38/23/39; (C7) 30/26/44; (C8) 33/20/47; (C9) 36/19/45 and (C10) 34/20/46. The leaching tests were performed according to ABNT-NBR 10005, while the compressive strength tests were made according to ABNT-NBR 5738. The results showed that specimens with composition C1, C2 and C3 did not have enough structural integrity to proceed with the other tests. In the leaching tests the result obtained for the pure residue was 1.34 mg / L U, and for compositions with the minimum Residue / Cement ratio equal to or less than C5 were <0.1 mg / L U. The maximum mechanical strength obtained was 19,04 ± 3,74 MPa for composition C10 and the minimum was 3.98 ± 1.28 MPa for C4. Thus, it can be said that Portland CP2 cement is a potential component for the immobilization of uranium present in the waste and the mechanical strength is sufficient for an arrangement that requires the stacking of the immobilized material.